Revolutionizing learning: leveraging social media platforms for empowering open educational resources / Erny Arniza Ahmad - Ahmad, Erny Arniza (UiTM Press, 2024)
This study explores the realm of Social Media - Open Educational Resources (SM-OERs) and their impact on education. SM-OERs is a novel approach that combines open educational resources (OERs) with social media platforms. Their primary goal is to provide accessible and captivating educational materials, cultivating a dynamic learning environment. SM-OERs framework embraces social media as a tool to enhance learning, engagement, and growth. The benefits of SM-OERs include enhanced learner engagement, collaboration, and personalized learning. By using the interactive nature of social media, learners can access educational content in a way that suits their preferences and pace. The cost-effectiveness and accessibility of SM-OERs make quality education available to a wider audience, transcending geographical limitations. However, challenges arise with using SM-OERs in education. Concerns about privacy and data security emerge when integrating social media platforms in learning settings. Ensuring the credibility and quality of educational content shared via SM-OERs is crucial to uphold the learning process's integrity. Despite these challenges, SM-OERs hold promise for education's future. The interactive and collaborative aspects of social media foster peer-to-peer learning, building a sense of community among learners. SM-OERs also offer a budget-friendly approach to education, reducing the need for expensive infrastructure and learning systems.